CleverSecure ONLINE System - Ab. Kadir, Shamimi (Universiti Teknologi PETRONAS, 2008)
CleverSecure Online System (COS) implements on the use of popular algorithm which is Blowfish algorithm to encrypt and decrypt the data that can be save in directory or send through email. This application also can encrypt the folder that contains the private information such as business plan etc. The purpose ofthe development is to provide the security service to the all information in our PC and allow users to protect confidential sensitive messages and documents sent over insecure medium of Internet. With data encrypted such that only the intended recipients can decrypt and read it, it prevents others from accessing the confidential information. The system also enables users to attach the encrypted file into their email to send directly to the receiver. The email system used to send the encrypted file to the third party. During the development of COS, the specific methodology used which is Prototyping Process. It contains several phase; Requirement Analysis; Preliminary Design; Prototype Creation; Evaluation; Prototype Refinement; and lastly Final Delivery. The outcome of this project is the online system that enable user to use the application easily with the friendly user interface to secure their private information.